In cellulo crystallization of Trypanosoma brucei IMP dehydrogenase enables the identification of genuine co-factors - Karol Nass (Nature Portfolio, 2020)
Trypanosoma brucei inosine-5′-monophosphate dehydrogenase (IMPDH) is an enzyme in the guanine nucleotide biosynthesis pathway and of interest as a drug target. Here the authors present the 2.8 Å room temperature structure of TbIMPDH determined by utilizing X-ray free-electron laser radiation and crystals that were grown in insect cells and find that ATP and GMP are bound at the canonical sites of the Bateman domains.